THREAT OF COVID-19 AND PERCEIVED STRESS: THE MEDIATING ROLE OF CHALLENGE, UNCONTROLLABILITY AND STRESSFULNESS: Threat of COVID-19 And Perceived Stress - Bilal, Ahmad; Aamir, Minahil (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the mediating role of challenge, uncontrollability, and stressfulness in predicting perceived stress from threat during COVID-19 pandemic in the general public.Study Design: Cross-sectional survey.Place and Duration of Study: Bahawalpur City, from Mar to May 2020.Methodology: A total of 360 participants (men=154, women=206) were recruited from different cities of Punjab province. The stress appraisal measure, perceived stress scale, and coping scale were administered through Google forms using social media platforms. The participation in the online survey implied signing the written informed consent available in the survey.Results: The primary and secondary appraisals of challenge (IE=0.84, SE=0.27, 95% LL=0.31, 95% UL=1.40), uncontrollability (IE=1.03, SE=0.36, 95% LL=0.34, 95% UL=1.76), and stressfulness (IE=-0.28, SE=0.12, 95% LL=-0.56, 95% UL=-0.08) fully mediated the relationship between threat of COVID-19 and perceived stress. Additionally, there was statistically significant positive relationship between threat of COVID-19 and use of coping strategies (r=0.14, p